Behavioural Economics dalam Era Digital: Mengapa Konsumen Semakin Rentan terhadap Impulse Buying.? (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to examine the behavioural economics perspective explains consumers' growing vulnerability to impulse buying in the digital era. The research employs a literature review method with a qualitative approach and descriptive analysis. Data were collected from Google Scholar and various relevant scientific sources, including ScienceDirect and ResearchGate, covering the period from 1972 to 2026. Technical aspects of data analysis through data reduction, categorisation of themes, interpretation of findings, and the preparation of a literature review. The initial search identified 50 articles, which were then screened based on topic relevance, source quality, and alignment with the research objectives, resulting in 43 articles selected for analysis. The findings indicate that impulse buying behavior is influenced by bounded rationality, cognitive biases, emotional responses, and nudging mechanisms embedded within digital environments. Various features such as personalized recommendations, live shopping, promotional notifications, user reviews, and product scarcity strategies have been shown to strengthen spontaneous purchasing impulses. Case studies of Shopee 11.11, TikTok Shop Live Shopping, and Alibaba Singles' Day demonstrate how digital technologies effectively leverage consumers' psychological characteristics to increase transaction volumes. This study confirms that behavioural economics provides a more comprehensive framework than the rational economic approach in explaining consumer behavior in the digital era.